Инглиз тилини ўргaниш жaрaёнидa тaлaбaлaрнинг мaдaниятлaрaрo aлoқaлaрини тaкoмиллaштиришнинг пeдaгoгик шaртлaри - Менлимуратова, Э.А (SCIENCE and SOCIETY, 2023)
The article discusses the pedagogical conditions for the development of intercultural relations among students, neces- sary for the development of foreign language competence among students, takes into account such factors as the needs and requirements of higher professional education, educational conditions.
Keywords: student; intercultural; English language; communication; language; consciousness; worldview; national; group; education; condition